2022
DOI: 10.1177/23247096221129470
|View full text |Cite
|
Sign up to set email alerts
|

Disease Control Achieved Using Atezolizumab + Bevacizumab in a Patient With Sarcomatoid Hepatocellular Carcinoma (SHCC), a Rare Variant Excluded From the IMbrave150 Trial

Abstract: Sarcomatoid hepatocellular carcinoma (SHCC) is a rare variant of liver cancer that lacks treatment options. The IMbrave trail demonstrated the efficacy of atezolizumab and bevacizumab (A + B) in patients with unresectable hepatocellular carcinoma but excluded patients with sarcomatoid variants. Herein, we describe a case of disease control achieved using the IMbrave regimen in a patient with sarcomatoid hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Fencer et al. ( 37 ) reported a case of unresectable SHC, where the patient achieved disease control for over a year after receiving atezolizumab and bevacizumab; this warrants further investigation of this combination (of antiangiogenic therapy and immunotherapy). Although numerous studies have reported various potential therapeutic targets and cases have been effectively treated with TKI and anti-PD-1 antibodies in the clinic, a clear basis for recommending the use of these regimens (or guiding drug selection) is currently lacking.…”
Section: Discussionmentioning
confidence: 97%
“…Fencer et al. ( 37 ) reported a case of unresectable SHC, where the patient achieved disease control for over a year after receiving atezolizumab and bevacizumab; this warrants further investigation of this combination (of antiangiogenic therapy and immunotherapy). Although numerous studies have reported various potential therapeutic targets and cases have been effectively treated with TKI and anti-PD-1 antibodies in the clinic, a clear basis for recommending the use of these regimens (or guiding drug selection) is currently lacking.…”
Section: Discussionmentioning
confidence: 97%